Unconventional translation initiation factor EIF2A is required for Drosophila spermatogenesis. Issue 2 (29th July 2021) - Lowe, David D.; Montell, Denise J.
Abstract: Background: EIF2A is an unconventional translation factor required for initiation of protein synthesis from non‐AUG codons from a variety of transcripts, including oncogenes and stress related transcripts in mammalian cells. Its function in multicellular organisms has not been reported. Results: Here, we identify and characterize mutant alleles of the CG7414 gene, which encodes the Drosophila EIF2A ortholog. We identified that CG7414 undergoes sex‐specific splicing that regulates its male‐specific expression. We characterized a MiMic transposon insertion that disrupts the coding regions of all predicted isoforms and is a likely null allele, and a PBac transposon insertion into an intron, which is a hypomorph. The MiMic allele is homozygous lethal, while the viable progeny from the hypomorphic PiggyBac allele are male sterile and female fertile. In dEIF2A mutant flies, sperm failed to individualize due to defects in F‐actin cones and failure to form and maintain cystic bulges, ultimately leading to sterility. Conclusions: These results demonstrate that EIF2A is essential in a multicellular organism, both for normal development and spermatogenesis, and provide an entrée into the elucidation of the role of EIF2A and unconventional translation in vivo. Key Findings: The unconventional translation initiation factor EIF2A is required for organismal viability in Drosophila. Drosophila EIF2A undergoes sex‐specific splicing. Reduced EIF2A expression causes male sterility. Drosophila EIF2A is required for individualization during spermatogenesis.